2014
DOI: 10.4049/jimmunol.1302068
|View full text |Cite|
|
Sign up to set email alerts
|

Exosomes Derived from Burkitt’s Lymphoma Cell Lines Induce Proliferation, Differentiation, and Class-Switch Recombination in B Cells

Abstract: Exosomes, nano-sized membrane vesicles, are released by various cells and are found in many human body fluids. They are active players in intercellular communication and have immune-suppressive, immune-regulatory, and immune-stimulatory functions. EBV is a ubiquitous human herpesvirus that is associated with various lymphoid and epithelial malignancies. EBV infection of B cells in vitro induces the release of exosomes that harbor the viral latent membrane protein 1 (LMP1). LMP1 per se mimics CD40 signaling and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(93 citation statements)
references
References 51 publications
2
91
0
Order By: Relevance
“…Computational analysis of the differentially expressed proteins predicted that LMP1-modified exosomes would affect molecular and cellular functions of cell growth and proliferation, cellular movement, cell death and survival, development, and cell-to-cell signaling (2). These predictions were corroborated by three independent studies demonstrating that LMP1-modified exosomes do indeed enhance proliferation, migration, invasion, and B cell differentiation toward a plasmablast-like phenotype when incubated with noninfected cells (13)(14)(15). Together, these data suggest that EBV-infected cells can manipulate the tumor microenvironment and contribute to the pathogenesis of EBV-associated cancers through the transfer of LMP1-modified exosomes.…”
supporting
confidence: 67%
“…Computational analysis of the differentially expressed proteins predicted that LMP1-modified exosomes would affect molecular and cellular functions of cell growth and proliferation, cellular movement, cell death and survival, development, and cell-to-cell signaling (2). These predictions were corroborated by three independent studies demonstrating that LMP1-modified exosomes do indeed enhance proliferation, migration, invasion, and B cell differentiation toward a plasmablast-like phenotype when incubated with noninfected cells (13)(14)(15). Together, these data suggest that EBV-infected cells can manipulate the tumor microenvironment and contribute to the pathogenesis of EBV-associated cancers through the transfer of LMP1-modified exosomes.…”
supporting
confidence: 67%
“…In our study model, B cells showed a high level of uptake, possibly due to the B cell origin of the lymphoma exosomes, supporting the idea of uptake specificity given the exosomes were collected primarily from cells originating from B cell lymphoma disease. These findings are in line with those of Hazan-Halevy et al 45 and Gutzeit et al 54 concerning B cells and Riches et al 55 in their work with breast tissue. In this study, we observed that DLCL2 exosomes were taken up rapidly and preferentially into CD19+ B lymphocytes and CD14+ monocytes.…”
supporting
confidence: 82%
“…In contrast, it is a widely accepted view that exosomes derive from cytoplasmic vesicles. Be a Burkitt's lymphoma cell or a prostatic adenocarcinoma cell, their exosomes are visibly generated in cytoplasmic vesicles [113,116,119]. However, exosome genomics are characterized by the presence of all classes of microRNAs that must have derived from the nucleolus, the physiological site where ribosomes are generated.…”
Section: Are the Tumor Cell Microvesicular Exosomes Distantly Relatedmentioning
confidence: 99%
“…All cells, but excessively the dedifferentiated cancer cells, release exosomes. Examples here are Burkitt's lymphoma [113], glioblastoma [114,115] (Fig. 5), and prostatic adenocarcinoma [116] exosomes.…”
Section: Are the Tumor Cell Microvesicular Exosomes Distantly Relatedmentioning
confidence: 99%